Human Capital, Brain Drain Syndrome and Its Implication on Socio-Economic Development in Nigeria: A Study of Lagos State (2015-2023) - Olayinka Babatunde Adebogun; Obodoeze Chekwube Josephine; Tunmise Daramola; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2024)
This study discusses the importance of investing in human capital for a nation's socio-economic development. It highlights how human resources are more critical to a country's growth than natural resources or physical capital. It is an asset that contributes to economic stability, growth, and worldwide recognition. Nigeria, with its abundant human and natural resources, has the potential for sustained economic progress. However, the country also experiences various forms of international migration, with many Nigerians migrating to other countries for education and work opportunities. The Diaspora community comprises a significant number of skilled professionals that contribute to the growth and development of their host countries. The objective of the study is to examine the nature and causes of the migration of human capital, and brain drain in Nigeria. The study adopts the push-pull theory that was propounded in 1966 by Everett Spurgeon Lee. Also, data was collected using qualitative method and 11 interviewees were interviewed while data were also collected from secondary sources. The result of the study reveals that the government's neglect of human capital investment has reduced economic growth and caused citizens to seek opportunities abroad. The study concludes by emphasizing the need for investment in human capital development through employment, training, healthcare, infrastructural development and technological advancement to eradicate brain drain and foster a more inclusive society. This study recommends the diversification of its economy, reduce corruption and invest in human capital development.